PROSES TEMU KEMBALI INFORMASI DI PERPUSTAKAAN SD ISLAM AL AZHAR 21 PONTIANAK - Nurhidayah, Ismi; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was motivated by the desire of researchers to find out the process information retrieval in the Al Azhar Islamic Elementary School Library 21 Pontiank. The purpose of this study was to find out how the process of information retrieval and the use of catalogs and classification as a means of retrieval of information in the Library of Al Azhar Islamic elementary school  21Pontianak. In this study the researcher used descriptive method with qualitative research. Data collection was done through observation, interview, and documentation at Library of Al Azhar Elementary Islamic School 21Pontianak. The results showed that the process of information retrieval in the library Al Azhar Islamic Elementary School21 Pontianak does not have a catalog as an information retrieval tool because according to librarians in the school library it is difficult to apply catalogs as information retrieval tools and no need to use catalogs as information retrieval tools because students do not understand the catalog. Catalogae and classifications are very important in the process of information retrieval, there are attempts to use catalogs in the Al Azhar Islamic Elementary School 21Pontianak but there are obstacles in cataloging, that was time. Because in cataloging had many processes or stages.       Keywords: Information Retrieval, Catalog, Classification